PENGARUH KARAKTERISTIK PERUSAHAAN TERHADAP TINGKAT LEVERAGE PADA PERUSAHAAN PUBLIK DI BURSA EFEK JAKARTA - Azib Asro'i (Universitas Islam Bandung, 2005)
The objective of this research is to identify the effect of firm characteristics (firm size, and asset growth, and profitability) simultaneously and individually on leverage rate at public firm of manufacturer sector listed in Jakarta Stock Exchange (BEJ).According to the objective, this research are explanatory research, is done by survey method on public firm of manufacturer sector listed in Jakarta Stock Exchange (BEJ) with firm population amount of 157. The minimal samples were taken in the amount of 84 firms based on Yamane method.This research used cross section data in the year at 2001 – 2003. This study used Multiple Regression Model, Furnished with tests on classical assumptions, such as multicollinearity, heteroscedasticity, and autocorrelation.Based on multiple regression model of analysis, the result aare that firm characteristics (firm size, and asset growth, and profitability) simultaneously and individually have influence on leverage rate at public firm of manufacturer sector listed in Jakarta Stock Exchange (BEJ) Keyword : Firm Characteristics and Leverage rate